The Impact of PTAs on the Duration of Antidumping Protection - Prusa, Thomas J.; Zhu, Min (World Bank, Washington, DC, 2021)
This paper examines the impact of preferential trade agreements on the duration of antidumping protection. It employs a two-step selection model where the first step accounts for the impact of preferential trade agreement membership on the original antidumping determination, and the second step estimates the impact of preferential trade agreement membership on the duration of duties. Several key findings emerge from the analysis. Most importantly, the duration of antidumping protection is significantly shorter for preferential trade agreement members, compared with targeted countries that are not preferential trade agreement members. The estimates imply that preferential trade agreement membership is associated with a 30 percent reduction in the duration of protection. Second, the impact on duration depends, in part, on whether the preferential trade agreement has rules specifically related to antidumping. On average, over all users and targeted countries, the impact on duration is about twice as large for preferential trade agreements with rules, compared with those with- out rules (and both have shorter duration than non-preferential trade agreement members). Third, the duration of antidumping measures has increased markedly over time, primarily due to cases in the right tail of the distribution. This is consistent with the widespread belief that the Uruguay Round's sunset review provisions did not produce the result that many World Trade Organization members sought, but it also reflects the growing fraction of cases targeting China. Although the rising fraction of cases against China partly explains why duration has increased, it does not explain the finding with respect to the impact of preferential trade agreements and duration.